High‐Gain 200 ns Photodetectors from Self‐Aligned CdS–CdSe Core–Shell Nanowalls. Issue 20 (30th March 2018) - Xu, Jinyou; Rechav, Katya; Popovitz‐Biro, Ronit; Nevo, Iftach; Feldman, Yishay; Joselevich, Ernesto
Abstract: 1D core–shell heterojunction nanostructures have great potential for high‐performance, compact optoelectronic devices owing to their high interface area to volume ratio, yet their bottom‐up assembly toward scalable fabrication remains a challenge. Here the site‐controlled growth of aligned CdS–CdSe core–shell nanowalls is reported by a combination of surface‐guided vapor–liquid–solid horizontal growth and selective‐area vapor–solid epitaxial growth, and their integration into photodetectors at wafer‐scale without postgrowth transfer, alignment, or selective shell‐etching steps. The photocurrent response of these nanowalls is reduced to 200 ns with a gain of up to 3.8 × 10 3 and a photoresponsivity of 1.2 × 10 3 A W −1, the fastest response at such a high gain ever reported for photodetectors based on compound semiconductor nanostructures. The simultaneous achievement of sub‐microsecond response and high‐gain photocurrent is attributed to the virtues of both the epitaxial CdS–CdSe heterojunction and the enhanced charge‐separation efficiency of the core–shell nanowall geometry. Surface‐guided nanostructures are promising templates for wafer‐scale fabrication of self‐aligned core–shell nanostructures toward scalable fabrication of high‐performance compact photodetectors from the bottom‐up. Abstract : A facile approach is proposed for the site‐controlled synthesis of horizontally aligned CdS–CdSe core–shell nanowalls with abrupt epitaxial interfaces and predictable aligned shells on insulating sapphire surfaces, and accordingly for a wafer‐scale fabrication of high‐gain 200 ns photodetectors without postgrowth transfer, alignment, or selective shell‐etching steps.